India : another millennium? - Thapar, Romila (New Delhi : Penguin, 2000)
On democratic and just society; essays on challenges before India in the twenty-first century.
Includes index.
BBS
Keywords: Business & finance; India -- Politics and government -- 1977-; India -- Social conditions -- 1947-